The Relationship between FLT-3 mutation and the response to treatment in children with acute myelocytic leukemia - منصور, لينا; عثمان حمدان (Latakia University Journal -Medical Sciences Series, 2023)
Background: Acute Myelocytic Leukemia (AML) is a rare disease with annual diagnosis of new cases about (500-600) case/year in USA, and (30-45) cases according to the statistics of the unversity children hospital in Damascus . The surviving rates in the patients of AML are still modest in the last three decades and doen’t exceed of (30-40%). The modification in the systems of the diagnosis and the chemotherapy and the supportive care have improved the prognosis of the patients who have acute myelocytic leukemia in the last years significantly . However , a high rate of children don’t respond to the first line treatment or they relapse , and they need to undergoing a new treatments . So the need was highlighted to discover new agents other than chemotherapy in the last years to overcome drug-related complications of resistance and toxicity . among these agents is the identification of the molecular mutations and the cytogenetic abnormalities and their diagnostic and therapeutic relevance to acute myelocytic leukemia warning . FLT-3 is tumor gene of the receptors for tyrosine kinas class 3 . who interfers with the basic stages of the hematopoiesis. Such as reproduction, differentiation and survival . in the recent years , the FLT-3 mutations become important marker in the hematological malignancy , and they have a prominent and distinguished role in the acute myelocytic leukemia as these mutations have been associated with clinical prognosis , treatment , and survival in children . We will analyze the occurrence of these mutations in patients with acute myelocytic leukemia with its differnt subtypes .and determine their prevalence rate in the AML patients , and will study their prognostic value and their relationship to response to treatment . Methods : the study we are doing is a prospective , longitudinal, interventional , diagnostic , cohort study . The study includes a sample size consisting of (49)patients who have been diagnosed withe acute myelocytic leukemia who were referred to the university children’s hospital and BASMA Association Support children with Cancer in 2019, and have a normal karyotype The patients were followed up by conducting an analysis PCR to identify the FLT-3 Mutations and then studying the prevalence of these mutations and the relationship of their presence to response to treatment . Results :the study showed that there is no real statistically significant correlation between the presence of mutations and the response to treatment at the end of the INDUCTION stage according to the resulting probability value (P –VALUE= 0.380) Conclusions : It is necessary to evaluate FLT-3 mutations in patients with acute myelocytic leukemia befor starting treatment . and conduct other studies in order to evaluate the relationship of the presence of FLT-3 mutations with the rate of survival (os) and the event –free rate (EFS) in AML Patients , because that might enable us to formulate a better treatment plan and know the prognostic aspects in each case .